Enabling Factors for Effective Implementation and Sustainability of Community-Based Rehabilitation (CBR) in Malaysia (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigates the enabling factors that contribute to the effective implementation and sustainability of Community-Based Rehabilitation (CBR), locally known as Program Pemulihan Dalam Komuniti (PDK), in Malaysia. Despite the expansion of PDK centres nationwide, challenges remain in sustaining high-quality rehabilitation services. Drawing on prior literature, this research examines the roles of workforce motivation, caregiver support, stakeholder collaboration, community participation, and service accessibility in fostering programme continuity. A qualitative methodology involving semi-structured interviews and focus group discussions with key stakeholders provided in-depth insights into operational and social determinants of PDK sustainability. The findings reveal that motivated and well-trained staff, active caregiver engagement, strong multi-stakeholder partnerships, inclusive community involvement, and accessible services are critical factors underpinning effective implementation. Workforce motivation and stakeholder collaboration emerged as particularly influential, shaping both programme quality and long-term viability. The study further highlights the need for structured caregiver support and enhanced service accessibility to ensure equitable rehabilitation outcomes. These results have implications for national policy and programme design, aligning with the United Nations Sustainable Development Goals (SDGs) by promoting inclusive education (SDG 4), decent work (SDG 8), good health and well-being (SDG 3), reduced inequalities (SDG 10), and partnerships for the goals (SDG 17). The research contributes to the literature by integrating human, social, and institutional factors into a comprehensive sustainability framework for PDK.